HUBUNGAN KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. POS INDONESIA (Persero) - Hayati, Isra’ (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This study aimed to determine the relationship of leadership to employee performance at PT. Pos Indonesia (Persero) Medan, to determine the relationship of compensation to employee performance at PT. Pos Indonesia (Persero) Medan, to determine the relationship of leadership and compensation to employee performance at PT. Pos Indonesia (Persero) Medan. Â Analysis techniques used in this study, multiple linear regression testing, Classical Assumption Test, t test, F test and the coefficient of determination. The analysis showed that the influence of leadership compensation variable (X1) on the performance (Y) is indicated by t count equal to 6,886 with 0,000 sig probability is smaller than 0.05. This means that the null hypothesis (Ho) is rejected and (Ha) is received it can be concluded that the leadership (X1) partially have a significant influence on employee performance (Y). effect of variable compensation (X2) on the performance (Y) is indicated by t count of 6943 with 0,000 sig probability is smaller than 0.05. This means that the null hypothesis (Ho) is rejected and (Ha) is received it can be concluded that the compensation (X2) partially have a significant influence on employee performance (Y). While the magnitude of the impact that indicated by the value of the coefficient of determination value of research results is 0.925 or 92.5% showed approximately 92.5 performance variable (Y) is influenced leadership (X1) and compensation (X2). The remaining 7.5% are influenced by variables not examined in this study.